Pengaruh Pemediasi Komitmen Organisasional dalam Hubungan antara Budaya Organisasi dengan Intent to Leave - Lintang Anugrah Nasution; T. Lyza T. Chairunnisa; Sunaryo Sunaryo (Universitas Bumigora, 2021)
This study aims to determine the effect of organizational culture on organizational commitment, organizational culture on Intent to Leave, organizational commitment to Intent to Leave and organizational culture on Intent to Leave through organizational commitment. The population in this study were 114 respondents and using saturated sampling techniques. The analysis technique used is path analysis. The results showed that organizational culture has a positive and significant effect on organizational commitment, organizational culture has a positive and significant effect on intent to leave, organizational commitment has no significant effect on intent to leave and there is no direct influence between organizational culture on intent to leave through organizational commitment.